Calculated inflammatory markers derived from complete blood count results, along with routine laboratory and clinical data, predict treatment failure of acute peritonitis in chronic peritoneal dialysis patients. Issue 1 (31st December 2023) - Zhou, Dan; Yang, Huibin; Zeng, Li; Yang, Wei; Guo, Fujia; Cui, Wenting; Chen, Cong; Zhao, Jiayao; Wu, Shuran; Yang, Ning; Lin, Hongli; Yin, Anchun; et al.
Abstract: Background & Aims: Complete blood count (CBC)-derived inflammatory markers are predictive biomarkers for the prognosis of many diseases. However, there was no study on patients with peritoneal dialysis-associated peritonitis (PDAP). We aimed to investigate the value of these markers in predicting treatment failure of acute peritonitis in chronic PD patients. Methods: The records of 138 peritonitis episodes were reviewed and divided into treatment success or failure groups in a single center for 10 years. CBC-derived markers and other routine data were recorded before peritonitis treatment was initiated. Univariate and multivariate regression analyses and the receiver operating characteristic (ROC) curve about the predictors of treatment outcomes were performed. Results: Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic immune-inflammation index (SII), and derived NLR were significantly higher in the failure group. Univariate logistic regression results showed that NLR and PLR were risk factors of treatment outcomes. The backward stepwise multivariate logistic regression results demonstrated that NLR [adjusted odds ratio (aOR), 1.376; 95% confidence intervals (CI), 1.105–1.713; p = .004], PLR (aOR, 1.010; 95%CI, 1.004–1.017; p = .002) were risk factors, but hemoglobin-to-lymphocyte ratio (HLR) (aOR, 0.977; 95%CI, 0.963–0.991; p = .001), and SII (aOR, 0.999; 95%CI, 0.998–1.000; p = .040) were protective factors. A combination of age, PD vintage, Gram-positive peritonitis, staphylococcus aureus, culture-negative, NLR, PLR, HLR, and SII would improve prognostic performance. The area under this ROC curve was 0.85, higher than other factors. Conclusions: NLR, PLR, HLR, and SII were associated with PDAP outcomes. Age, PD vintage, NLR, and PLR were significant risk factors in PDAP patients.